Therapeutic targeting of HCMV-encoded chemokine receptor US28: Progress and challenges - Berg, Christian; Rosenkilde, Mette M. (Frontiers in Immunology, 2023)
The pervasive human cytomegalovirus (HCMV) causes significant morbidity in immunocompromised individuals. Treatment using the current standard-of-care (SOC) is limited by severe toxic adverse effects and anti-viral resistance development. Furthermore, they only affect HCMV in its lytic phase, meaning viral disease is not preventable as latent infection cannot be treated and the viral reservoirs persist. The viral chemokine receptor (vCKR) US28 encoded by HCMV has claimed a lot of attention in recent years. This broad-spectrum receptor has proven to be a desirable target for development of novel therapeutics through exploitation of its ability to internalize and its role in maintaining latency. Importantly, it is expressed on the surface of infected cells during both lytic and latent infection. US28-targeting small molecules, single-domain antibodies, and fusion toxin proteins have been developed for different treatment strategies, e.g. forcing reactivation of latent virus or using internalization of US28 as a toxin shuttle to kill infected cells. These strategies show promise for providing ways to eliminate latent viral reservoirs and prevent HCMV disease in vulnerable patients. Here, we will discuss the progress and challenges of targeting US28 to treat HCMV infection and its associated diseases.